Sufficient Scope in Current Aircraft Technology Developments? - Alexander R.C. de Haan (European Journal of Transport and Infrastructure Research, 2010)
Air travel demand is growing worldwide with an approximate worldwide long term average of 5 to 6% annually. This growth has both very positive and negative effects. Aviation is deeply embedded in our society. Dramatic decrease in ticket prices has brought to many the possibility of reaching many destinations worldwide in a day’s travel. It is claimed by some that the negative effects – such as noise pollution and greenhouse gas emissions - will not become more problematic in the future, because technologies are being developed that will compensate them. The starting point of this research is to discover whether this claim concerning the potential of current aircraft technology developments is true. In other words: is the current development in aircraft technology capable to contribute to a sustainable development in the aviation sector by keeping current positive effects, while mitigating the negative effects? Existing research on this issue is mostly trend research, focussing at the average technology efficiency increase and extrapolating this to the future. In a context where multiple actors have to decide about what to do, this extrapolation is not enough. An aggregated number does not reveal the concrete options and causal relations behind it. This paper, therefore, introduces the open and explicit method of systems analysis to answer the question if (and if so, how) new aircraft technology can mitigate the adverse effects of an increasing air travel demand, while keeping the benefits. It presents analytical results in terms of numbers and score cards in order to feed the policy process that eventually should lead to policy in order to solve the problem. In light of the results of the systems analysis, this paper concludes that current developments in aircraft technology are not sufficient to mitigate the adverse effects of growth. Our research suggests that the combination of the efficiency improvement rate, the growth rate of the demand for air travel, and the long replacement times for older technology do in fact not cancel each other out. In order to achieve a sustainable development in the aviation sector, this systems analysis approach shows the limited (though important) influence technology can have on the full concept of sustainable development. We suggest to not only invest more into developing ever better technologies, but to also search for non-technical solutions in order to address the full concept of sustainable development.